Valproic Acid in Parkinson's Disease: A Friend or Foe? - Gelbard, Amos (British Journal of Healthcare and Medical Research, 2025)
There have been several reports of Parkinson's disease like symptoms being a side effect of Valproic Acid use. Valproic Acid is a drug prescribed for Epileptic seizures and also as a mood stabilizer. Despite the said reports of Parkinson's like side effects, several other studies had shown it to in fact be neuroprotective and perhaps therapeutic against PD in vivo. This review will center around these few studies, bring their results and ask for more experimentation to solve this issue of whether Valproic Acid triggers Parkinson's or perhaps triggers a healing from it. I would hypothesize in this essay that perhaps the supposed PD-like symptoms from VA use are on the other side of the spectrum, for example that PD tremor is being countered by Valproic Acid stiffness which puts an emphasis on its ideal dosage.